2009
DOI: 10.1093/jjco/hyp035
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Phase II/III Trial Comparing Hepatectomy Followed by mFOLFOX6 with Hepatectomy Alone as Treatment for Liver Metastasis from Colorectal Cancer: Japan Clinical Oncology Group Study JCOG0603

Abstract: A randomized controlled trial is being conducted in Japan to compare hepatectomy alone with hepatectomy followed by adjuvant chemotherapy as treatment in patients with curatively resected liver metastases from colorectal cancer to improve survival with intensive chemotherapy. Between 42 and 70 days after liver resection, patients are randomly assigned to either hepatectomy alone or hepatectomy followed by 12 cycles of modified FOLFOX6 (mFOLFOX6) regimen. A total of 300 patients (including 78 patients in Phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 4 publications
2
43
0
Order By: Relevance
“…The most common site of recurrence in the present study was the liver (50%; 15/30), followed by the lung (30%; 9/30) and both the liver and lung (10%; 3/30). Additionally, relapse generally occurred within the first 2 years after surgery (80%; 24/30), similarly to the results of other studies [21]. Therefore, we suggest that close observation with follow-ups at short intervals is necessary for the first 2 years following surgery.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The most common site of recurrence in the present study was the liver (50%; 15/30), followed by the lung (30%; 9/30) and both the liver and lung (10%; 3/30). Additionally, relapse generally occurred within the first 2 years after surgery (80%; 24/30), similarly to the results of other studies [21]. Therefore, we suggest that close observation with follow-ups at short intervals is necessary for the first 2 years following surgery.…”
Section: Discussionsupporting
confidence: 88%
“…However, these data are not yet sufficient to propose this treatment as standard. Several prospective trials are currently ongoing to test the efficacy of oxaliplatin-based chemotherapy after complete resection [21]. …”
Section: Discussionmentioning
confidence: 99%
“…The National Comprehensive Cancer Network guidelines recommend multidisciplinary treatment combining hepatectomy and chemotherapy such as FOLFOX for the management of liver metastases (32). At present, the Japan Clinical Oncology Group (JCOG) is currently conducting a randomized phase II/III study (JCOG0603) comparing surgery alone with surgery plus mFOLFOX6 therapy after curative resection of liver metastasis from colorectal cancer (33).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning chemotherapy in Stage IV patients, Nordlinger et al reported that either 6 preoperative or postoperative cycles of FOLFOX4 improved 3-year progression-free survival (PFS) by 8–9% in CRC patients with up to 4 liver metastases compared to no perioperative chemotherapy [14]. A randomized phase II/III study in Japan, JCOG0603, started in spring 2007, it aims to address the superiority of postoperative mFOLFOX6 to surgery alone in CRC patients with an unlimited number of resectable liver metastases [15]. In terms of lung metastasis, all studies conducted before 2004 reported that after curative resection of pulmonary metastases from CRC, chemotherapy was not a prognostic factor by multivariate analysis [16].…”
Section: Discussionmentioning
confidence: 99%